UPAYA KOMISI PEMILIHAN UMUM UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT PADA PEMILIHAN UMUM LEGISLATIF DI KOTA SURAKARTA - Nidia, Rizma Dwi; Maharani, Andina Elok Puri (Res Publica: Jurnal Hukum Kebijakan Publik, 2018)
This study examines the implementation of Law Number 7 of 2017 concerning General Elections related to the role of the General Elections Commission (KPU) to increase public participation in legislative elections. The purpose of this study was to find out how the implementation of Law Number 7 of 2017 concerning Elections related to the role of the General Election Commission for its efforts to increase public participation in the Legislative General Election in Surakarta City in order to achieve the set targets. This type of research is empirical research and the data used are primary data and secondary data. The research location was carried out at the KPU of  Surakarta City. The efforts made by the KPU of Surakarta to increase public participation are by using the Voter Socialization and Education method which is considered to attract the attention of the community and is done by adjusting based on the needs of each segmentation of society.